Endoscopic diagnosis of gastric intestinal metaplasia in patients with autoimmune gastritis using narrow-band imaging: does pseudopyloric metaplasia muddy the waters? - Dilaghi, Emanuele; Esposito, Gianluca; Pivetta, Giulia; Galli, Gloria; Pilozzi, Emanuela; Annibale, Bruno; Lahner, Edith (Endoscopy International Open, 2022)
Background and study aims In autoimmune atrophic gastritis (AAG), associated with intestinal (IM) and/or pseudopyloric metaplasia (PPM), endoscopic surveillance is recommended for gastric cancer risk mainly linked to IM. Endoscopic Grading of Gastric Intestinal Metaplasia (EGGIM) reliably identifies IM, but has not been assessed in AAG. We aimed to assess the performance of EGGIM (index test) versus histology (reference test) of corpus IM in AAG.Patients and methods This was a cross-sectional study of 210 AAG patients undergoing surveillance gastroscopy with narrow-band imaging (NBI): corpus IM scored according to EGGIM, histology according to updated Sydney system, and morphological criteria.Results NBI identified corpus IM in 88.6 % of AAG patients: EGGIM were 0, 1, 2, 3, 4 in 11.4 %, 0.5 %, 33.3 %, 1.9 %, and 52.9 %, respectively. Histology identified corpus IM in 78.1 % and PPM in 79.5 % of patients. PPM was present with IM in 57.6 % and without IM in 21.9 % patients, 20.5 % had IM without PPM. EGGIM, compared to histology, correctly classified 76.2 % of patients, showing high sensitivity (91.5 %, 95 %CI 86.1–95.3). EGGIM correctly classified 93 % of patients with IM without PPM, 90.9 % with both metaplasias, and 21.7 % with PPM without IM yielding low specificity (21.7 %, 95 %CI 10.9–36.4).Conclusions In AAG, EGGIM showed high accuracy and sensitivity identifying > 90 % of patients with histological corpus IM. EGGIM overestimated IM when PPM without IM was present, yielding low specificity. These findings raise the question of whether in AAG, PPM and IM may display similar endoscopic features on NBI.